2021
DOI: 10.1016/j.celrep.2021.109624
|View full text |Cite
|
Sign up to set email alerts
|

SMS2 deficiency impairs PKCδ-regulated B cell tolerance in the germinal center

Abstract: Highlights d Sgms2 À/À and Aicda-Cre/Prkcd f/f mice exhibit similar B cell and lupus-like phenotypes d SMS2 is highly upregulated and promotes PKCd-mediated apoptosis in anti-DNA GC B cells d B cells from patients with lupus have abnormally low SMS2 expression d Pharmacologic activation of SMS2 attenuates lupus pathogenesis in NZBWF1 mice

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 75 publications
4
18
0
Order By: Relevance
“…Although lupus patients with PRKCD mutations are rare, our study of the regulation of PKCδ activity supports that a deficit in PKCδ nuclear translocation in GC B cells is actually a common abnormality in lupus [48]. We discovered that PKCδ nuclear translocation in GC B cells is activated by SMS2, whose expression is drastically decreased in lupus patients' B cells [48].…”
Section: Pkcδ Regulates Gc B Cell Tolerancesupporting
confidence: 69%
See 3 more Smart Citations
“…Although lupus patients with PRKCD mutations are rare, our study of the regulation of PKCδ activity supports that a deficit in PKCδ nuclear translocation in GC B cells is actually a common abnormality in lupus [48]. We discovered that PKCδ nuclear translocation in GC B cells is activated by SMS2, whose expression is drastically decreased in lupus patients' B cells [48].…”
Section: Pkcδ Regulates Gc B Cell Tolerancesupporting
confidence: 69%
“…Notably, in both studies mentioned above, PKCδ nuclear translocation was found to be induced in cultured B cells, but was not in untouched naïve B cells, suggesting that some type of metabolic stress induced by culturing was promoting PKCδ nuclear localization. We reported that although naïve B cells contain much more cellular PKCδ than GC B cells, nuclear PKCδ was observed in GC B cells but was almost undetectable in naïve B cells [48], supporting that in vivo, PKCδ nuclear translocation and its tolerance activity is unique to GC B cells.…”
Section: Pkcδ Is Involved In B Cell Tolerancesupporting
confidence: 68%
See 2 more Smart Citations
“…Therefore, the use of current MACS protocols is limited if GC formation is irresponsive to SRBC challenge due to gene mutations, or SRBC challenge affects the intended downstream studies. In addition, compared to FACS-purified GC B cells, the purities of MACS-isolated untouched GC B cells from immunized mice are relatively low ( Ramezani-Rad and Rickert, 2021 ), which often necessitates further enrichment by FACS via antibody labeling of MACS-enriched GC B cells, depending on the application ( Ou et al., 2021 ).…”
Section: Before You Beginmentioning
confidence: 99%